Gestão da qualidade e sua relação com a satisfação e o comprometimento no trabalho de servidores técnico-administrativos - Schaumann, Gustavo Pucci (2010)
This study aims at analyzing the possible relations between the implementation of criteria and practices of the Excellence Model of public management (GESPÚBLICA Model) and the satisfaction and work commitment of managerial and technical civil servants at a public organization in Fortaleza (CE Brazil). The GESPÚBLICA Model was developed by the federal government of Brazil through the Ministry of Planning, budget and management and integrates the National Programme for combating the bureaucracy in the public service. It is a transposition of Total Quality Management practices from private to public organizations. This dynamic brought new expectations for the considered civil servants in relation to the administration and work conditions. The main theoretic references were the Neoclassical School of Administration, the System and Development oriented Psychology, the Working Group on Organizational and Work Psychology (GTPOT) and the Political Economics of Power and Organizational Studies. The field research was conducted in the Regional Labour Superintendence of the state of Ceará (Brazil) (a specific unity of the Ministry of Labour and Employment that was awarded for various years and recognized as a reference in the application of this model). The research contributed to investigate the consequences of the strategies, practices and the learning of quality in satisfaction and commitment of administrative technical servants in the period of 1997 to 2007. As method of research, a quantitative approach was used while a structured questionnaire served as research instrument. The data analysis considered the relation of the implementation of the Excellence Model in public management with the variables of satisfaction in the process of work organization, management and planning, working environment, values and culture, financial remuneration and benefits and commitment at work in its affective, calculative and normative dimensions. The final considerations of the investigation indicate the limited relation between the initiatives of the model with the satisfaction and the commitment at work.